2006
DOI: 10.3748/wjg.v12.i45.7233
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer and the immune system: The role of tumor invading T cells

Abstract: Colon cancer is still one of the leading causes of cancer death worldwide. Although the host immune system has been shown to react against tumor cells, mainly through tumor infiltrating lymphocytes and NK cells, tumor cells may utilize different ways to escape anti-tumor immune response. Tumor infiltration of CD8+ and CD4+ (T-bet+) effector T cells has been attributed to a beneficial outcome, and the enhancement of T cell activation through T cell receptor stimulation and co-stimulatory signals provides promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 79 publications
4
49
0
2
Order By: Relevance
“…It is now becoming clear that the tumor microenvironment, which is largely orchestrated by inflammatory cells, is an essential participant in the neoplastic process, promoting proliferation, survival, and migration. For this reason many studies have been focused on the evidence of the role of inflammation in carcinogenesis recently (Waldner et al, 2006, Roxburgh et al, 2010Unal et al, 2013). Generally, studies described that lymphopenia means an impaired cell-mediated immunity, while neutrophilia is linked response to systemic inflammation (Zahorec et al, 2001).…”
Section: Pretreatment Neutrophil/lymphocyte Ratio As a Prognostic Aidmentioning
confidence: 99%
“…It is now becoming clear that the tumor microenvironment, which is largely orchestrated by inflammatory cells, is an essential participant in the neoplastic process, promoting proliferation, survival, and migration. For this reason many studies have been focused on the evidence of the role of inflammation in carcinogenesis recently (Waldner et al, 2006, Roxburgh et al, 2010Unal et al, 2013). Generally, studies described that lymphopenia means an impaired cell-mediated immunity, while neutrophilia is linked response to systemic inflammation (Zahorec et al, 2001).…”
Section: Pretreatment Neutrophil/lymphocyte Ratio As a Prognostic Aidmentioning
confidence: 99%
“…Colitis-associated cancer is characterized by a dense infiltrate of immune cells, including macrophages, dendritic cells and T cells, which include the subset of CD8 þ and CD4 þ (T-bet þ ) effector T cells and CD4 þ CD25 þ T cells (Waldner et al, 2006). However, the functional role of these immune cells is only recently beginning to be unveiled.…”
Section: Immune Cells In Cacmentioning
confidence: 99%
“…The reasons for this increased cancer occurrence are not fully understood, but there is ample evidence from murine models that the presence of chronic inflammation provides an environment that favors the growth of neoplastic cells (9)(10)(11)(12)(13). Thus, in recent studies of a murine model of colitis, dextran sodium sulfate-induced colitis (DSS-colitis), it was shown that the inflammation is a necessary antecedent for the induction of colon tumors by a carcinogenic agent, azoxymethane (AOM) (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%